MONETARY POLICY CREATES MACROECONOMIC STABILITY - Visokavičienė, Birutė (Ekonomika, 2010)
The study of monetary policy concentrates on the systematic analysis of the interaction between the major monetary policy targets and macroeconomic indicators as signals to policymakers about possible changes which may influence the macroeconomic stability. In this respect, the purpose of this article is to justify the arguments supporting the role and importance of monetary policy and its proximate targets for ensuring macroeconomic stability. The object of the study is the impact of monetary policy on macroeconomic changes.The method is analysis of monetary theory, scientific literature and documents. Such a methodological position enables justification of the influence of the key targets of the monetary policy on the global economic processes related to inflation, finance stability and economic growth.